MULTIMEDIA FACILITIES AS A SUPERVISION EFFORT OF MINORS IN SOCIAL MEDIA: SERVING AT ‘SEKOLAH PRESTASI’ PERSPECTIVES ON THE ITE LAW - Cindy Kang; Hari Sutra Disemadi (Universitas Internasional Batam, 2022)
The Covid-19 pandemic that occurred in Indonesia indirectly made internet technology even more needed, especially for school children who implemented Online School or commonly called online learning. It is undeniable that internet facilities not only have a positive impact, but also have negative impact on minors, such as hoax, pornographic content, and cyber crimes. This study uses empirical juridical methods, and the data used in this study are primary data obtained from field data and observations from the Prestasi Elementary School. Based on the results of this study, it is found that 75% of the parents/guardians of Prestasi Elementary Students did not understand the substance of Electronic Information and Transaction Law (ITE Law). The result obtained from this study are that knowledge and understanding of the ITE Law plays a crucial role for parents/guardian of Prestasi Elementary Students in supervising their children on social media. Therefore, literacy education is needed for parents/guardians of students so they can supervise their children to avoid any negative impacts on social media. Multimedia facilities can increases awareness and understanding of parents/guardians of Prestasi Elementary School related to the ITE Law.